STRATEGY OF RELIGIOUS EDUCATION TEACHERS IN STRENGTHENING RELIGIOUS MODERATION AMONG STUDENTS AT STATE SENIOR HIGH SCHOOL 1 SAUSU - Anita Novi Yanti; Hamlan, Hamlan; Hamka, Hamka; Ardiyansyah, Ardiyansyah (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2024)
The aim of this paper is to investigate the strategy of religious education teachers in strengthening religious moderation among students at State Senior High School in Sausu District. This used a case study qualitative method. Data were gathered through direct observation, in-depth interview, and written document analysis. In-depth interview involving the school principal, religious teachers, and students. This study concluded that teachers of religious education have implemented various strategies to instill the values of religious moderation in students through classroom learning, daily practices, teacher role modeling, and extracurricular activities. The values emphasized include balance (At-Tawassuth), reflected in equal treatment for all religious adherents and fostering a harmonious relationship between religious practices and social life without extremism. Justice (Al-I’tidal) is practiced through fairness toward others, maintaining environmental cleanliness, and ensuring equal treatment for all students, regardless of their religious backgrounds